Impact of Program Review in Canadian Post-secondary Education: A Qualitative Case Study - Sauvé, Claire; Hoare, Alana; Ramirez, Gloria (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2026)
Using a qualitative case study research design, this study examined the phenomenon of program review at a mid-sized vocational college in British Columbia, Canada, and the experiences of five department leaders and program coordinators engaging in program review. The study sought to answer the following questions: What is the experience of faculty and program coordinators leading the program review process? Is the program review meaningful? Is the program review manageable? Can a program review process be both meaningful and manageable? Are the meaningfulness and manageability of program review in conflict with one another? Participants recognized the potential impact of program review in terms of creating space for analytic and critical reflection to interrogate the influence of reviews on institutional strategic planning, advocacy for departmental and institutional resources, and assessment of program viability within the broader academic mission of the institution. However, complex power dynamics at play within program review for improvement versus for accountability were highlighted as a point of tension and resistance that prevents the realization of the ideals of program review.